One hundred most cited articles related to Endoscopic retrograde cholangiopancreatography: A bibliometric analysis - Xu, Xuan; Guan, Lulu; Wu, Yao; Ke, Huajing; Zhao, Yuanbin; Liu, Pi (Frontiers in Surgery, 2022)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) has developed over the past few decades into a reliable technology for diagnostic and therapeutic purposes. Through a bibliometric analysis, this research attempted to evaluate the characteristics of the top 100 articles on ERCP that had the most citations. Methods: We extracted pertinent publications from the Web of Science Core Collection (WoSCC) on July 9, 2022. The top 100 ERCP articles with the most citations were identified and analyzed. The following data were extracted: publication year, country/region, organization, total citation times, annual citation times, research type and research field, etc. To implement the network's visual analysis, a bibliographic coupling network based on keywords was built using the VOSviewer 1.6.17 program. Results: The journal with the most publications were GASTROINTESTINAL ENDOSCOPY, with 45 articles. Most of the top 100 articles came from the United States (n = 47) and Italy (n = 14). Indiana University and the University of Amsterdam were among the most important institutions in ERCP research. ML Freeman of the University of Minnesota contributed the highest number (n=9) and the most highly cited paper. The age of the paper and article type is closely related to citation frequency. Of the 100 most-cited articles, clinical application in the field of ERCP has focused on three aspects: diagnosis, treatment, and complications. Clinical use of ERCP has shifted from diagnosis to treatment. Post-ERCP pancreatitis is the focus of attention, and the clinical application of technically complex therapeutic ERCP is the future development trend. Conclusion: This study lists the most influential articles in ERCP by exposing the current state of the field and showing the evolution of research trends to provide perspective for the future development of ERCP.